[PP.04.05] COMPATIBILITY OF LEFT VENTRICULAR HYPERTROPHY DIAGNOSED BY ELECTROCARDIOGRAPHY AND BY ECHOCARDIOGRAPHY: THE NORTHERN SHANGHAI STUDY. (September 2017) - Zhou, Y.; Yu, S.; Bai, B.; Lv, Y.; Xiong, J.; Teliewubai, J.; Ji, H.; Fan, X.; Chi, C.; Xu, Y.; Zhang, Y.
Abstract : Objective: To investigate the compatibility of left ventricular hypertrophy (LVH) diagnosed by electrocardiography and by echocardiography. Figure. No caption available. Design and method: Echocardiography and electrocardiography were applied to define LVH in 1599 elderly Chinese aged >65 years old in communities located at the northern Shanghai. Echocardiographic LVH (ECHO-LVH) was defined by left ventricular mass indexed for Body Surface Area (LVM/BSA) or indexed for height2.7 (LVM/height2.7). Electrocardiographic LVH (ECG-LVH) was defined by Sokolow-Lyon (SL), Cornell and Cornell Product (CP) criteria. LVH was defined by LVM/BSA > 125 g/m 2 in males, >110 g/m 2 in females (LVH1); LVM/BSA > 115 g/m 2 in males, > 95 g/m 2 in females (LVH2); and LVM/height2.7 > 51 g/m 2 .7 in males, > 47 g/m 2 .7 in females (LVH3). Results: In the correlation analysis, CP had the greatest correlation coefficient compared with SL and Cornell, in males (0.22 vs. 0.20 & 0.19 for LVM/BSA and 0.21 vs. 0.18 & 0.19 for LVM/height2.7), in females (0.16 vs. 0.08 & 0.15 for LVM/BSA and 0.18 vs. 0.05 & 0.17 for LVM/height2.7) and in total population (0.19 vs. 0.14 & 0.17 for LVM/BSA and 0.16 vs. 0.08 & 0.16 for LVM/height2.7). In Chi-square analysis, only LVH diagnosed by SL was significantly associated with LVH diagnosed by echocardiography. Moreover, CP criterion had the greatest area under curve of ROC than Cornell criterion and the SL index (0.62 vs. 0.58 & 0.54 in LVH1, 0.62 vs. 0.55 & 0.51 in LVH2 and 0.62 vs. 0.57 & 0.51 in LVH3). Conclusions: In ECG LVH criteria, CP criterion complies better than SL index and Cornell criterion in assessing cardiac hypertrophy.